Environmental & architectural phenomenology. Vol. 12 issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 2001)
Vol. 12, No. 1, Winter 2001 (includes “items of interest,” “references received,” book review of Joachim-Ernst Berendt's The Third Ear: Listening to the World, essays by Justin Wikler, Hildegard Westerkamp & Darren Copeland, and poem by Judyth Hill).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals